2017
DOI: 10.1021/acs.analchem.6b02909
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Quantification of Bionanoparticles by Electrospray Differential Mobility Analysis: An Application to Lipoprotein Particle Concentration Measurements

Abstract: This study presents an upgraded electrospray differential mobility analysis (ES-DMA) setup for the absolute quantification of bionanoparticle concentrations in biological samples, with a special focus on non-high-density-lipoprotein particle concentrations (non-HDL-P). Metrological characterization of the system's analytical performances for concentration measurements shows that the mean intermediate precision relative standard deviation is 14% for biological samples, 6% for silica nanoparticles, and less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…However, as mentioned before, such material is not commercially available. Our study additionally highlighted the fact that E probably depends on the physico-chemical characteristics of the particles and on the conductivity of the analyzed samples [23] Either way, it appears that E is specific for a given sample and that its value may not be transferable to any sample regardless of sample composition and of the entity being measured. These observations thus indicate that using a reference material made of inorganic monodisperse particles with certified number concentration may not be suitable to measure E for lipoproteins in biological samples due to the physico-chemical differences of biological and inorganic matrices.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…However, as mentioned before, such material is not commercially available. Our study additionally highlighted the fact that E probably depends on the physico-chemical characteristics of the particles and on the conductivity of the analyzed samples [23] Either way, it appears that E is specific for a given sample and that its value may not be transferable to any sample regardless of sample composition and of the entity being measured. These observations thus indicate that using a reference material made of inorganic monodisperse particles with certified number concentration may not be suitable to measure E for lipoproteins in biological samples due to the physico-chemical differences of biological and inorganic matrices.…”
mentioning
confidence: 58%
“…Analyses being performed at ambient pressure and temperature, small variations of these parameters may also induce small variations of the gas viscosity, then impacting flow-rates in the system and again, number size distribution measurements [17]. However, we demonstrated that the major parameter contributing to the uncertainty budget associated to absolute lipoprotein quantification by ES-DMA was the ES transmission efficiency E, i.e., the percentage of aerosolized particles that are actually detected and counted by the system compared to the initial particle number concentration in the colloidal suspension [23,24].…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…the concentration in the initial sample. Various approaches have been reported, but to date, debates remain concerning the most adapted method and harmonization of the process have not yet been achieved [86,89,90].…”
Section: Electrospray Differential Mobility Analysis (Es-dma)mentioning
confidence: 99%
“…Contrary to most methods reported for lipoprotein profiling and quantification, ES-DMA is the only one for which the measurand is the full intact lipoprotein [91]. However, it was demonstrated that calibration with appropriate standards is necessary to achieve accurate quantification and a study of results comparability with IN revealed important variability depending on the calibration material chosen [90]. As for diameter measurement accuracy, ES-DMA systems are generally calibrated with CRMs of inorganic nanoparticles and provide highly precise measurements [90,92].…”
Section: Electrospray Differential Mobility Analysis (Es-dma)mentioning
confidence: 99%